The determinants of personal saving: A study in Malaysia / Norsyamimi Che Ibrahim - Che Ibrahim, Norsyamimi (2011)
In this study, a number of variables that could affect personal saving are examined using regression to show how they are related to personal saving. The objectives of this study are to study the determinant relationship between terms of trade and personal saving, real GDP and personal saving, and between personal income and personal saving. Data that are collected in this study is by using the main source that is the secondary data. The empirical study was performed using the time series data of the Malaysia between the years 1970 until 2007. The result shows that personal saving is dependent on terms of trade, real GDP and personal income. Therefore, finding reveal independent variables which are terms of trade, real GDP and personal income is significant with dependent variable which is personal saving